Propriedades de durabilidade de concreto autoadensável leve com agregado reciclado - Amorim , Tassyano Feitosa de (2016)
Self-compacting concrete is considered one of the greatest developments in concrete technology. Lightweight concrete reduces the builder's own weight, heat transfer, and improves sound insulation. And the use of recycled aggregates should be one of the practices of the construction industry due to the scarcity of natural raw materials. However, the joint use of these technologies requires the need to verify their performance in the materials. The objective of this study was to obtain and analyze the properties of self-compacting lightweight concrete with and without recycled aggregates, focusing on concrete performance against reinforcement corrosion in structural elements without structural purposes. This work consisted in the production of two lightweight self-compacting concretes, one with natural aggregates and the other with recycled aggregates, and their research on durability (Figg, CAIM and carbonation). The lower concrete specific mass was achieved by the use of recycled concrete block aggregates and air-entraining additives. The superplasticizers and viscosity modifier additives were used to guarantee self-compactibility. The substitution of natural aggregates by recycled concrete block aggregates was intended for use in non-structural elements, where armature rates are low and generally have high coverings, such as concrete-fence panels. As a result, CALAR increased the void index and low density favoring its applicability, but it increased water absorption rate and decreased tensile strength, compression and corrosion protection. Both concretes presented high air permeability when evaluated by test parameters for conventional concretes. In addition, the kinetics of the corrosion process, by chloride ions, was more accentuated by the substitution of the natural aggregates by recycled aggregates than by the thickness of the cover.